If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+3-1=2(2x-2)-2x
We move all terms to the left:
4x+3-1-(2(2x-2)-2x)=0
We add all the numbers together, and all the variables
4x-(2(2x-2)-2x)+2=0
We calculate terms in parentheses: -(2(2x-2)-2x), so:We get rid of parentheses
2(2x-2)-2x
We add all the numbers together, and all the variables
-2x+2(2x-2)
We multiply parentheses
-2x+4x-4
We add all the numbers together, and all the variables
2x-4
Back to the equation:
-(2x-4)
4x-2x+4+2=0
We add all the numbers together, and all the variables
2x+6=0
We move all terms containing x to the left, all other terms to the right
2x=-6
x=-6/2
x=-3
| 5x-5-(4x-8)=20x+20 | | 2p-20=-2p+20 | | 5(2x+3)=95x | | 324=(x)(x-3)(x+12) | | x=(x)(x-3)(x+12) | | 4d/9d+1/9=2/3 | | 4x+12-2x=18+2x-3 | | 20x=75000 | | 1570=12×h | | 1=(m-3/4)+(m+3/5) | | 4-5x-39=0 | | 36-5x-x2=36 | | 2n-2+12=4n | | (5x+5)+73+67=180 | | 5x+7x=2x+30 | | 2n-2-12=4n | | 15x=7=12x-5 | | 8k^2-10k-10=0 | | 7.3^2=2x^2 | | Tx1/3=7/10 | | 6y+5y=8y+11 | | 6y+5y=8y×11 | | X+0.17x=1200 | | 4y+2=(y-2)=8 | | 2x+8-5x= | | 6x+(x+20)+8x+10=90 | | 4a+3a+6=20 | | 7+6x=-6x-101 | | 6x-(-15)=3 | | 8-2x=4+x | | 7x-7=9x+5 | | 6x+9=44+x |